Fabrication of ZnO Nanorods Structure for Drastically Enhancing Gas Sensing Response to NO2 Gas - Abood, Nabeel; Sable, Pradip; Yassen, Jamil; Dharne, Gopichand (Trends in Sciences, 2022)
In this report, zinc oxide thin film was successfully deposited on a glass substrate by using a simple and low-cost technique i.e. modified Successive Ion Layer Adsorption and Reaction (SILAR). Prepared zinc oxide thin film was characterized for its physical and chemical properties by using XRD diffraction, Field Emission Scanning Electron Microscopy (FESEM), energy dispersive spectroscopy (EDS), UV-VIS spectroscopy, Raman spectroscopy and Fourier transform infrared spectroscopy (FTIR). The results of structural and morphological properties show that the prepared film has wurtzite hexagonal structure with nanorods-like morphology. Gas sensing characteristics revealed that the prepared film was sensitive to NO2 gas. The response calculated at operating temperature 200 °C, was 1.37 when NO2 concentration was 10 ppm, the response increased when the NO2 concentration increased which reached to 2.16 when NO2 concentration was 80 ppm with short response and recovery time. HIGHLIGHTS Nanorods- like morphology of ZnO were fabricated via modified SILAR technique The ZnO nanorods exhibit high sensitive and short response/ recovery time for NO2 gas at operating temperature i.e. 200 °C The synthesis method and sensing behavior of synthesized ZnO nanorods- like morphology, revealed a promising candidate for fabricating low-consumption gas sensors GRAPHICAL ABSTRACT